1987
DOI: 10.3382/ps.0661147
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immune Responses in Broiler Chicks Fed Methionine-Supplemented Diets

Abstract: Effects of feeding supplementary methionine and choline on broiler growth and immunity were examined by supplementing a corn-soybean diet that contained 21% crude protein, 3,255 kcal metabolizable energy/kg diet, .35% methionine, .37% cystine, and .13% choline. Methionine (.063, .125, .25%) and choline (.125, .25%) were dietary variables. Sulfate (.055%) was added either alone or along with methionine (.125 or .25%) and choline (.125%). In one study, the .25% methionine diet was supplemented with .121% betaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(115 citation statements)
references
References 17 publications
9
104
1
1
Order By: Relevance
“…This correlation was also demonstrated in layer chickens (Gross and Siegel, 1980). Tsiagbe et al, (1987) suggested that the requirement for methionine for maximum antibody titers was greater than that for growth. Infections lead to several changes in amino acid plasma levels.…”
Section: Discussionmentioning
confidence: 49%
“…This correlation was also demonstrated in layer chickens (Gross and Siegel, 1980). Tsiagbe et al, (1987) suggested that the requirement for methionine for maximum antibody titers was greater than that for growth. Infections lead to several changes in amino acid plasma levels.…”
Section: Discussionmentioning
confidence: 49%
“…Both increase of globulin and decrease in albumin to globulin ratio are tied to an improved immune system function on broiler (Bovera et al 2015(Bovera et al , 2016 and can positively affect the health status of birds. The increase in protein and globulin due to the diet supplemented with 5EAAs may be partially due to arginine supplementation: in fact arginine was reported to protect animals against ammonia intoxication and disease and oxidative stress (Basiouni et al 2006;Bautista-Ortega et al 2013) and/or methionine (Tsiagbe et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary methionine supplementation induces increased T-cell-mediated immunocompetence in broiler chickens, Gallus domesticus (Tsiagbe et al 1987;Swain & Johri 2000). Recently, Soler et al (2003) showed that supplementing methionine to passerine (magpie, Pica pica) nestlings induces a higher T-cell-mediated immunocompetence and reduces growth.…”
Section: Introductionmentioning
confidence: 99%